Development and Validation of Instruments to Measure Students' E-Learning Readiness - Krismanto, Wawan; Aziz , Imam Nur; Pagarra, Hamzah; wandira, septiana; Puspitarini, Dwi (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to develop and validate the used instruments to measure students' readiness to participate in learning through learning management systems. This readiness is known as e-learning readiness. The tool was developed based on four components of e-learning readiness by Ayd & Tasci's model, namely technology, innovation, people, and self-development. The research sample was students of the Elementary School Teacher Education Study Program, Universitas Negeri Makassar. The research used quantitative survey methods. The instrument developed consisted of 36 statement items, with responses in the form of a five-choice Likert scale. The data analysis testing used Rasch modeling through the Winstep program. The results of the study managed to develop an instrument of e-learning readiness, which consisted of 29 items statements under the model. The results of data analysis also showed that the reliability of the respondents was 0.93 and classified as very good. For reliability items, the results of data analysis showed 0.97 and classified as excellent. The result of raw variance explained by the measure of 50.1% also indicates that the requirements for unidimensionality are quite fair; this means the stated instrument is good enough in measuring what should be measured. Overall, therefore, this study has produced a device of e-learning readiness that can predict the availability of following the learning process.